2013
DOI: 10.1523/jneurosci.4132-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Sensing Ion Channel-1a Is Not Required for Normal Hippocampal LTP and Spatial Memory

Abstract: Acid-sensing ion channel-1a (ASIC1a) is localized in brain regions with high synaptic density and is thought to contribute to synaptic plasticity, learning, and memory. A prominent hypothesis is that activation of postsynaptic ASICs promotes depolarization, thereby augmenting N-methyl-D-aspartate receptor function and contributing to the induction of long-term potentiation (LTP). However, evidence for activation of postsynaptic ASICs during neurotransmission has not been established. Here, we re-examined the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
77
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 25 publications
9
77
0
2
Order By: Relevance
“…If the extracellular Mg 2+ concentration was kept low in these experiments, LTP was normal in ASIC1a knockout animals, suggesting that the ASICmediated postsynaptic depolarization may increase NMDA receptor function by removing the Mg 2+ block. Another study inhibited ASIC1a with Psalmotoxin1 (PcTx1) or used a nervous system-specific ASIC1 knockout approach based on the Cre/Lox system with the Nestin promoter, which leads to the loss of ASIC1 expression at approximately embryonic day 10.5 and, consequently, to the absence of ASIC1a mRNA and ASIC1a currents in brain neurons (Wu et al, 2013). In contrast to previous work with ASIC1a 2/2 mice, Fig.…”
Section: Tissue Distribution Cellular Functions and Physiologimentioning
confidence: 99%
“…If the extracellular Mg 2+ concentration was kept low in these experiments, LTP was normal in ASIC1a knockout animals, suggesting that the ASICmediated postsynaptic depolarization may increase NMDA receptor function by removing the Mg 2+ block. Another study inhibited ASIC1a with Psalmotoxin1 (PcTx1) or used a nervous system-specific ASIC1 knockout approach based on the Cre/Lox system with the Nestin promoter, which leads to the loss of ASIC1 expression at approximately embryonic day 10.5 and, consequently, to the absence of ASIC1a mRNA and ASIC1a currents in brain neurons (Wu et al, 2013). In contrast to previous work with ASIC1a 2/2 mice, Fig.…”
Section: Tissue Distribution Cellular Functions and Physiologimentioning
confidence: 99%
“…In previous studies of hippocampal brain slices, extracellular field potential recordings suggested impaired hippocampal long-term potentiation (LTP) in ASIC1a −/− mice (20), although another study did not detect an effect of ASIC1a (33). Another study using microisland cultures of hippocampal neurons suggested that the probability of neurotransmitter release increased in ASIC1a −/− mice (32).…”
mentioning
confidence: 98%
“…ASICs in central neurons are mainly composed of homomeric ASIC1a and heteromeric ASIC1a/2a (3)(4)(5)(6) and ASIC1a/2b (7). Genetic ablation of ASIC1a has indeed led to the conclusion that ASICs contribute to long-term potentiation and memory formation (2), but a more recent study challenged these findings (8). In contrast to our incomplete understanding of the physiological functions of ASICs, there is a comparatively large body of evidence that activation of ASIC1a-containing channels in pathophysiological states that are associated with sustained acidosis contributes to neuronal or axonal degeneration (9,10).…”
mentioning
confidence: 99%